Molecularly Distinct NLRP3 Inducers Mediate Diverse Ratios of Interleukin-1β and Interleukin-18 from Human Monocytes. (22nd October 2020) - Midtbö, Kristine; Eklund, Daniel; Särndahl, Eva; Persson, Alexander
Abstract : Inflammasomes cleave and activate interleukin- (IL-) 1 β and IL-18 which have both shared and unique biological functions. IL-1 β is an important mediator of the acute phase response to infections and tissue damage, whereas IL-18 takes part in activation and tailoring of the adaptive immune response. While IL-1 β has served as the prototypic indicator of inflammasome activation, few studies have compared the potential differences in IL-1 β and IL-18 production during inflammasome activation. Since these cytokines partake in different immune pathways, the involvement of inflammasome activity in different conditions needs to be described beyond IL-1 β production alone. To address a potential heterogeneity in inflammasome functionality, ATP, chitosan, or silica oxide (SiO2 ) were used to induce NLRP3 inflammasome activation in THP-1 cells and the subsequent outcomes were quantified. Despite using doses of the inflammasome inducers yielding similar release of IL-1 β, SiO2 -stimulated cells showed a lower concentration of released IL-18 compared to ATP and chitosan. Hence, the cells stimulated with SiO2 responded with a distinctly different IL-18 : IL-1 β ratio. The difference in the IL-18 : IL-1 β ratio for SiO2 was constant over different doses. While all downstream responses were strictly dependent on a functional NLRP3 inflammasome, the differences did not depend on the level of gene expression, caspase-1 activity, or pyroptosis. We suggest that the NLRP3 inflammasome response should be considered a dynamic process, which can be described by taking the ratio between IL-1 β and IL-18 into account and moving away from an on/off perspective of inflammasome activation.